Mass balance, metabolic disposition, and pharmacokinetics of a single IV dose of [14C]CA102N in HT-29 xenograft athymic nude mice - Tchaparian, Eskouhie; Lin, Hua-Yang; Chen, Yuchih; Hunter, J. Neil; Yin, Sindy; Ng, Huey; Wu, Albert (Frontiers in Pharmacology, 2024)
CA102N is a novel anticancer drug developed by covalently linking H-Nim (N-(4-Amino-2phenoxyphenyl methanesulfonamide) to Hyaluronic Acid to target CD44 receptor-rich tumors specifically. This design seeks to enhance efficacy and overcome limitations associated with H-Nim, including poor solubility and short half-life. This investigation aimed to establish the pharmacokinetics, distribution, and metabolism of CA102N and quantitatively characterize its tumor permeability in xenograft mice following a single intravenous dose of 200 mg/kg [14C] CA102N. Liquid scintillation counting analysis was used to determine the pharmacokinetics and mass balance, while metabolite profiling was completed using HPLC-MS coupled with a radio flow-through detector. Quantitative Whole-Body Autoradiography was used to assess tissue distribution. Concentrations of CA102N and its metabolites were measured using total radioactivity data from urine, feces, and tissue samples. The results indicated that 94.9% of the administered dose was recovered at 240 hours post-dose. The primary route of radioactivity elimination was through urine, accounting for an average of 77% of the dose, while 13.2% was eliminated via feces. Tissue distribution showed rapid accumulation within 0.5 hours postadministration, followed by rapid decline in most tissues except for the tumor, where slow elimination was observed. CA102N/metabolites exhibited a two-phase pharmacokinetic profile, characterized by an initial rapid distribution phase and a slower terminal elimination, with a halflife (t 1/2 ) of about 22 h. The mean maximum concentration (C max ) of 1798.586 µg equivalents per ml was reached at 0.5 hours (T max ). Most of the radioactivity in plasma was attributed to CA102N, while small-molecule hydrolysis products dominated the excreta and tissue samples. Metabolite profiling revealed two major hydrolysis products: H-Nimdisaccharide and H-Nim-tetrasaccharide. No unchanged [14C] CA102N was detected in urine or feces, suggesting that CA102N undergoes extensive metabolism before excretion. In conclusion, the current data provided valuable insights into the Pharmacokinetics, metabolism, and tissue/tumor distribution of CA102N in mice. These findings demonstrated that metabolic clearance is the primary elimination pathway for CA102N and that the drug exhibits tumor retention, supporting its development as an anticancer therapy. Our results provided a strong pharmacological basis for the advancement of CA102N into the clinic.